Anxiety and Depression Symptoms in Children and Adolescents Who Stutter: A Systematic Review and Meta-Analysis. - Bernard, Ria; Hofslundsengen, Hilde; Norbury, Courtenay Frazier (Journal of Speech, Language & Hearing Research, 2022)
Purpose: The purpose of this study was to investigate whether there are elevated symptoms of anxiety or depression in children and adolescents (aged 2–18 years) who stutter, and to identify potential moderators of increased symptom severity. Method: We conducted a preregistered systematic review of databases and gray literature; 13 articles met criteria for inclusion. A meta-analysis using robust variance estimation was conducted with 11 cohort studies comparing symptoms of anxiety in children and adolescents who do and do not stutter. Twenty-six effect sizes from 11 studies contributed to the summary effect size for anxiety symptoms (851 participants). Meta-analysis of depression outcomes was not possible due to the small number of studies. Results: The summary effect size indicates that children and adolescents who stutter present with increased anxiety symptoms (g = 0.42) compared with nonstuttering peers. There were insufficient studies to robustly analyze depression symptoms, and qualitative review is provided. No significant between-groups differences were reported in any of the depression studies. Conclusions: Preliminary evidence indicates elevated symptoms of anxiety in some children and adolescents who stutter relative to peers. There was a tendency toward higher depression scores in this population, although reported between-groups differences did not reach statistical significance. These findings require replication in larger, preferably longitudinal studies that consider factors that may moderate risk. Nevertheless, our findings highlight a need for careful monitoring of mental health and well-being in young people who stutter.